Análise in vitro, in silico e in vivo dos efeitos antinociceptivos e anti-inflamatórios de dois triterpenos semissintéticos (CL-P2 e CL-P2A) - Passos, Maria Juliane (2020)
Semi-synthetic compounds obtained from natural products isolated from plants may represent interesting pharmacological tools in the bioprospecting of new drugs for the control of inflammatory pain. Combretum leprosum is a species found in the North and Northeast of Brazil and is used by the community as an anti-inflammatory agent. Among its isolated substances, triterpene 3β, 6β, 16β-tri-hydroxilup-20 (29) -ene (CL-1), obtained from the flowers of Combretum leprosum Mart, which has several biological activities. The aim of this study was to perform the in vitro, in silico and in vivo analysis of the activity of two semi-synthetic triterpenes (CL-P2 and CL-P2A) derived from CL-1. In vitro assays included cytotoxicity tests on murine fibroblasts (L929) and human keratinocytes (HaCaT) using the sulforodamine B staining method (SRB) after 24h, 48h and 72h. For the in silico tests CL-P2 and CL-P2A, they were designed in the MarvinSketch program, to obtain the SMILES code (Simplified Molecular Input Line Entry Specification). From this code, its pharmacokinetic and pharmacodynamic properties were obtained. For in vivo assays, 120 male Swiss mice (25-30g) were used. The in vivo activity of CL-P2 (0.1; 1 or 10 mg / kg) or CL-P2A (0.1; 1 or 10 mg / kg) was analyzed using the zymosan-induced abdominal contortion test. The mechanism of action of CL-P2 or CL-P2A was investigated by measuring the activity of myeloperoxidase (MPO) and Superoxide Dismutase (SOD) in addition to nitrite / nitrate levels. For acute and subacute toxicity tests, groups were treated (per os) daily with the highest effective dose of CL-P2 or CL-P2A (10 mg / kg) for 14 days. The results were expressed as mean ± SEM and p <0.05 was considered significant. The in vitro results demonstrated that CL-P2 and CL-P2A showed low cytotoxicity in the tested cell lines, however, at the highest concentrations (20 and 40 μg / mL), both compounds reduced cell growth, showing a cytostatic effect. In silico analyzes suggested that the enzymes cyclooxygenases 1 and 2 (COX-1 and COX-2) may be targets for CL-P2, whereas the mu-type 1 receptor could be a target for CL-P2A. In the zymosan-induced abdominal contortion model, both CL-P2 (1 or 10 mg / kg) (16.67 ± 2.17 and 9.16 ± 2.93, respectively) and CL-P2A (1 or 10 mg / kg) kg) (3.57 ± 1.17 and 4.83 ± 0.70, respectively) reduced the number of contortions when compared to the untreated group (33.50 ± 6.18). Investigating the mechanism of action, it was observed that none of the compounds CL-P2 (10 mg / kg) or CL-P2A (10 mg / kg) - reduced the influx of neutrophils into the peritoneal cavity, assessed indirectly by MPO activity (3 , 39 ± 0.83 and 3.68 ± 0.29, respectively), when compared to the untreated group (3.32 ± 0.29); however, the antinociceptive effect of CL-P2 was associated with a reduction in nitrite / nitrate levels (0.607 ± 0.009), while the antinociceptive effect of CL-P2A was associated with an increase in SOD activity (2.222 ± 0.113), when compared to the untreated group (nitrite 0.66 ± 0.01 and SOD 1.683 ± 0.008), respectively). Acute and subacute toxicity tests did not reveal evidence of changes when compared to the untreated group. CL-P2 and CL-P2A, acting by different mechanisms of action, reduce inflammatory pain and appear safe when administered to mice for 14 days, suggesting the efficacy and preclinical safety of CL-P2 and CL-P2A. Still, considering that its theoretical pharmacological targets are associated with the modulation of inflammatory pain, these data can support the bioprospecting of new drugs to control these events.